Cloning of human- interleukin-12 into pJET cloning vector for anti-cancer vaccine development - Che Ani, Muhamad Alhapis (2015)
The Newcastle disease virus can replicate rapidly and kill human cancer cells. Therefore it has the potential to be developed as a cancer vaccine. However, the immune system hinders the replication of the virus in these cells. In order to make it more efficient as a cancer vaccine, the the human interleukin-12 (hIL-12) gene will be cloned into the virus. However, before this gene can be transferred to the virus, it must first be cloned into a cloning vector. In this project, the hIL-12 gene was obtained from the plasmid pUNO-hIL12 and cloned into a pJET cloning vector. A set of forward and reverse primers with NheI restriction included was designed to amplify hIL-12 gene. This will lead to producing the hIL-12 gene fragment with NheI restriction sites after amplification by polymerase chain reaction (PCR) cycles. The PCR product was then purified by using MEGAquick-spinTM Total Fragment DNA Purification Kit. The purified hIL-12 was then cloned into pJET cloning vector by T4 DNA ligase and transformed into competent Escherichia. coli Top 10 cells by using heat-shock transformation method. The cloning was verified using NheI restriction enzyme digestion analysis and further confirmed by sequencing.